Prevalence of COVID-19 vaccine hesitancy in Brazil: a systematic review and meta-analysis - Daniele Melo Sardinha; Daniele Melo Sardinha; Marcos Jessé Abrahão Silva; Marcos Jessé Abrahão Silva; Sebastião Kauã de Sousa Bispo; Sebastião Kauã de Sousa Bispo; Alex Patrick Oliveira da Silva; Karla Valéria Batista Lima; Karla Valéria Batista Lima; Ilma Pastana Ferreira; Luana Nepomuceno Gondim Costa Lima; Luana Nepomuceno Gondim Costa Lima; et al. (Frontiers in Public Health)
IntroductionVaccines have long been one of the most effective strategies for public health during epidemics and pandemics caused by infectious diseases. Vaccine hesitancy is a public health problem that hinders the control of disease transmission. It refers to the refusal or reluctance to receive vaccines for various reasons, including sex, personal beliefs, cultural factors, and a lack of confidence in vaccine safety and efficacy. The COVID-19 pandemic was controlled using vaccines, but maintaining ideal vaccination coverage is essential to continue reducing hospitalizations and deaths from COVID-19. In Brazil, vaccination coverage did not reach the targeted goal, raising concerns about the ongoing impact of COVID-19.ObjectiveThe study aimed to investigate the prevalence of COVID-19 vaccine hesitancy in Brazil.MethodologyA systematic review with meta-analysis was carried out using the PubMed, Medline, LILACS, and ScienceDirect databases.ResultsIn the search, 238 articles were reviewed, of which 8 were found to be eligible for analysis. The prevalence of vaccine hesitancy was 13.3%, or 0.133 (95% CI = 0.082–0.208), in Brazil. In the subgroup analysis by pandemic wave, the first pandemic wave showed a prevalence of 13.6% or 0.136 (95% CI = 0.081–0.220), while the second pandemic wave had a prevalence of 11.4% or 0.114 (95% CI = 0.029–0.358). Due to heterogeneity, meta-regression showed a significant association between vaccine hesitancy and parents of children and adolescents (Q = 95.55; df = 2; p = <0.0001), indicating that vaccine hesitancy is significantly higher in this population compared to the general population and older adults. Fake news, lack of knowledge, personal beliefs, income, being a woman, being a young male individual without comorbidities, being married with older children, being older, and being asymptomatic were the main factors influencing vaccine hesitancy.ConclusionIn the first meta-analysis conducted in Brazil, vaccine hesitancy was more prevalent among parents of children and adolescents, and vaccine hesitancy decreased in the second pandemic wave. Public policies must be developed to address the factors that interfere with acceptance of the COVID-19 vaccine.